2020
DOI: 10.1029/2019gl086677
|View full text |Cite
|
Sign up to set email alerts
|

Auroral Omega Bands are a Significant Cause of Large Geomagnetically Induced Currents

Abstract: The strongest event of geomagnetically induced currents (GIC) detected by the North‐West Russian GIC network occurred during the main phase of the magnetic storm on 28 and 29 June 2013. Extremely high value, 120 A, was recorded in the 330 kV transformers on Kola Peninsula in the 04–07 magnetic local time (MLT) sector. The Defense Meteorological Satellite Program (DMSP) spacecraft took a sequence of ultraviolet (UV) auroral images in the southern hemisphere and observed multiple omega bands. The ionospheric equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…This is consistent with Sorathia et al (2020) who report that the high-resolution global MHD simulation GAMERA produced localized field-aligned current structures. Nevertheless, many observational studies have shown highly-complex ionospheric current features (Apatenkov et al, 2020) such as vortexes (Belakhovsky et al, 2019;Viljanen et al, 2006;Viljanen, Tanskanen, et al, 2006), which pose significant challenges for modelers. Especially since it is now becoming clear that models need to capture some of these features if they are to yield accurate regional predictions of geomagnetic disturbances.…”
Section: Latitudinal and Regional Variabilitymentioning
confidence: 99%
“…This is consistent with Sorathia et al (2020) who report that the high-resolution global MHD simulation GAMERA produced localized field-aligned current structures. Nevertheless, many observational studies have shown highly-complex ionospheric current features (Apatenkov et al, 2020) such as vortexes (Belakhovsky et al, 2019;Viljanen et al, 2006;Viljanen, Tanskanen, et al, 2006), which pose significant challenges for modelers. Especially since it is now becoming clear that models need to capture some of these features if they are to yield accurate regional predictions of geomagnetic disturbances.…”
Section: Latitudinal and Regional Variabilitymentioning
confidence: 99%
“…Early studies of the magnetic perturbations that are signatures of these transient ionospheric currents noted the small-scale character of these events (e.g., Viljanen, 1997), but many efforts to predict GICs have continued to focus on global processes (geomagnetic storms and substorms). Recent observational studies by Ngwira et al (2015Ngwira et al ( , 2018, Belakhovsky et al (2019), Dimmock et al (2019Dimmock et al ( , 2020, and Apatenkov et al (2020) have provided new evidence of the localized nature of the magnetospheric and/or ionospheric processes associated with these impulsive magnetic perturbations. This includes evidence of ionospheric current vortices, their close association with transient overhead north-south oriented auroral structures and poleward boundary intensifications, and information on the spatial scale size of individual events.…”
Section: Introductionmentioning
confidence: 99%
“…midnight interval sharp pulses were seen at different times at each site over a span of ~ 1.5 hours. Their multiple rapid variations resembled those of Pi 3 or Ps 6 pulsations (Opgenoorth et al, 1983;Solovyev et al, 1999;Apatenkov et al, 2020) rather than solitary impulses.…”
Section: Event Studiesmentioning
confidence: 89%
“…A recent paper by Apatenkov et al (2020) also provided detailed observations of a very large GIC that was associated with an interval of omega bands. They modeled this event using the sum of two basic current systems: a 1D linear current (mimicking the auroral electrojet) and a 2D vortex that passed eastward over the field of view of the ground magnetometers.…”
Section: Connection To Omega Bands and Their Physical Mechanismsmentioning
confidence: 99%